Polygenic risk scores indicate extreme ages at onset of breast cancer in female BRCA1/2 pathogenic variant carriers - Borde, Julika; Laitman, Yael; Blümcke, Britta; Niederacher, Dieter; Weber-Lassalle, Konstantin; Sutter, Christian; Rump, Andreas; Arnold, Norbert; Wang-Gohrke, Shan; Horváth, Judit; Gehrig, Andrea; Schmidt, Gunnar; et al. (BMC cancer, 2022)
Clinical management of women carrying a germline pathogenic variant (PV) in the BRCA1/2 genes demands for accurate age-dependent estimators of breast cancer (BC) risks, which were found to be affected by a variety of intrinsic and extrinsic factors. Here we assess the contribution of polygenic risk scores (PRSs) to the occurrence of extreme phenotypes with respect to age at onset, namely, primary BC diagnosis before the age of 35 years (early diagnosis, ED) and cancer-free survival until the age of 60 years (late/no diagnosis, LD) in female BRCA1/2 PV carriers.